The aspartate aminotransferase-like domain of Firmicutes MocR transcriptional regulators. (October 2015) - Milano, Teresa; Contestabile, Roberto; Lo Presti, Alessandra; Ciccozzi, Massimo; Pascarella, Stefano
Graphical abstract: Highlights: C-terminal domains of Firmicutes MocR cluster into three clades. Evolutionary analysis indicates conserved structural features. Each Firmicutes MocR clade is characterized by specific conserved residues. MocR effector binding site shares many features with PLP fold type-I enzymes. Differences with PLP enzymes may explain lack of catalytic activity Abstract: Bacterial MocR transcriptional regulators possess an N-terminal DNA-binding domain containing a conserved helix-turn-helix module and an effector-binding and/or oligomerization domain at the C-terminus, homologous to fold type-I pyridoxal 5′-phosphate (PLP) enzymes. Since a comprehensive structural analysis of the MocR regulators is still missing, a comparisons of Firmicutes MocR sequences was undertook to contribute to the understanding of the structural characteristics of the C-terminal domain of these proteins, and to shed light on the structural and functional relationship with fold type-I PLP enzymes. Results of this work suggest the presence of at least three subgroups within the MocR sequences and provide a guide for rational site-directed mutagenesis studies aimed at deciphering the structure-function relationships in this new protein family.